Effects of a stepwise alveolar recruitment maneuver on lung volume distribution in dogs assessed by computed tomography - Sanchez, Ana Flávia; Ambrósio, Aline Magalhães; Pinto, Ana Carolina B. C. Fonseca; Pereira, Marco Aurélio Amador; Andrade, Felipe Silveira Rego Monteiro; Rodrigues, Renata Ramos; de Carvalho Martins, Alessandro Rodrigues; Baroni, Carina Outi; Ferrante, Bruno; Fantoni, Denise Tabacchi (Frontiers in Veterinary Science, 2024)
Background Pulmonary atelectasis is a commonly occurs during anesthesia. In these cases, mechanical ventilation (MV) associated with alveolar recruitment maneuvers (ARMs) and positive end-expiratory pressure (PEEP) is indicated to reverse the condition, ensure adequate gas exchange and improve oxygenation. ARMs can trigger volutrauma, barotrauma, and atelectrauma. Therefore, computed tomography (CT) is the gold-standard method for monitoring lung aeration after ARM. Objective To evaluate lung volume distribution after stepwise ARMs using computed tomography (CT). Methods Twelve dogs weighing 24.0 ± 6.0 kg, aged 3 ± 1 years, of both sexes and different breeds, underwent orchiectomy or ovariohysterectomy. The animals were anesthetized and ventilated in volume-controlled mode. ARMs were then initiated by positive end-expiratory pressure (PEEP) titration (5, 10, 15, and 20 cmH2O). CT scans, cardiovascular parameters, and ventilatory mechanics were evaluated at all time points. Data were assessed for normality using the Shapiro–Wilk test and a two-way analysis of variance, followed by a post-hoc Bonferroni test to identify differences between time points. Statistical significance was attributed to a value of p of <0.05. Results CT demonstrated that the ARMs increased ventilation throughout the lung, including the dependent regions, with volumes that increased and decreased proportionally with PEEP titration. When they reached PEEP 10 and 5 cmH2O descending (d), they remained significantly higher than those in PEEP 0 cmH2O (baseline). Static compliance improved about 40% at PEEP 10d and PEEP 5d compared to baseline. There was an increase in heart rate (HR) from PEEP 15 increasing (i) (74.5%) to PEEP 10d (54.8%) compared to baseline. Mean arterial blood pressure (MABP) decreased approximately 9% from PEEP 15i to PEEP 15d compared to baseline. Conclusion Lung attenuation and regional and global volumes assessed by CT showed that maximum pulmonary aeration distribution followed by PEEP titration occurred at PEEP 20 cmH2O, maintaining the lungs normoaerated and without hyperaeration.